1994
DOI: 10.1295/polymj.26.1244
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Removing Japanese Encephalitis virus (JEV) and Gold Particles Using Cuprammonium Regenerated Cellulose Hollow Fiber (i-BMM or BMM) from Aqueous Solution Containing Protein

Abstract: We intended to clarify the mechanism of virus removal in aqueous protein solution and human plasma solution through conventional and high performance regenerated cellulose hollow fiber (i.e., BMM and i-BMM). We employed Japanese encephalitis virus (JEV) as a typical virus. Two kinds of disperse gold particles (GP) with different size were represented as model particles of a virus and protein particles. We investigated the filtration characteristics concerning removability of GP and JEV ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Past experimental observations have reported the phenomenon of virus breakthrough as a function of litres of filtrate/m 2 of filter area for a number of filters: Asahi Planova I‐BMM and Pall DV20 [11,12]. The present paper demonstrates for the first time that flux decline is a unifying parameter characterizing breakthrough.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Past experimental observations have reported the phenomenon of virus breakthrough as a function of litres of filtrate/m 2 of filter area for a number of filters: Asahi Planova I‐BMM and Pall DV20 [11,12]. The present paper demonstrates for the first time that flux decline is a unifying parameter characterizing breakthrough.…”
Section: Discussionsupporting
confidence: 57%
“…The primary aim of this study was to gain a better understanding of the process parameters that affect virus retention and ultimately to develop a scientific foundation for validation of virus filters. Previous studies with virus filters suggested that virus retention as well as liquid flow declines over the course of a filtration run [10,11]. Since two liquid flow‐related variables are changing over the course of filtration (the volume processed and the flow rate), initial work focused on understanding which of these parameters is more closely associated with virus retention.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have reported a significant decline in virus retention during the course of filtration through different parvovirus filters [2][3][4][5][6]. The underlying mechanisms controlling this loss of virus retention are still not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…(7). The Peclet number describes the relative importance of convective and diffusive solute transport through the membrane:…”
Section: Appendix Amentioning
confidence: 99%
“…In addition to non-destructive integrity tests, virus filters are also characterized by measuring the retention of model viruses [5], bacteriophage [6], or gold nanoparticles [7]. All of these methods are focused on providing information on the largest pores in the membrane, i.e., the pores that are most likely to compromise the virus retention characteristics of the filter.…”
Section: Introductionmentioning
confidence: 99%